Sharing Session dan Sosialisasi Media Pembelajaran Interaktif Bersama Anak-anak di SOS Children's Village Flores - Desak Made Anggraeni; Nasywa Meisha Putri; Maria Agustina Seneng; Andreas Pero Karwayu (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid advancement of information technology offers significant opportunities to transform the quality of education through interactive learning media. This community service initiative introduced science visualization via animated videos to children at SOS Children's Village Flores through a warm, engaging sharing session. The implementation process comprised three integrated stages: preparation, execution, and evaluation. During the implementation phase, the children explored topics such as SN1 and SN2 substitution reactions, metallic bonding, and air pollution using interactive and adaptive animated videos. The presentation of material was interspersed with two-way discussions and collective reflection. The activity generated great enthusiasm; the children responded actively and were able to contextualize abstract scientific concepts, making them more concrete. Animated videos can overcome the limitations of conventional classrooms, serving as a fun and inclusive learning tool. This approach sparks an interest in learning while strengthening the children's foundation in digital literacy from an early age.